High-field magnetoelasticity of Tm₂Co₁₇ and comparison with Er₂Co₁₇ - Andreev, A.V.; Zvyagin, A.A.; Skourski, Y.; Yasin, S.; Zherlitsyn, S. (Физика низких температур, 2017)
Acoustic properties (ultrasound velocity and attenuation) and magnetostriction were measured in pulsed fields up to 60 T applied along the c axis of Tm₂Co₁₇ single crystal. Similar to Er₂Co₁₇, the transition in Tm₂Co₁₇ is accompanied by clear anomalies in the sound velocity. The observed 0.3% jump of the sound velocity at the transition is negative in Tm₂Co₁₇, whereas it is positive in Er₂Co₁₇. The magnetostriction at the transition also differs very much from that in Er₂Co₁₇. In Tm₂Co₁₇, the transition is accompanied by a smooth minimum of 0.15 × 10−4 in longitudinal magnetostriction whereas in Er₂Co₁₇ by a very sharp expansion of much larger magnitude (1.2 × 10−4). In the transverse mode, the effect in Tm₂Co₁₇ looks as very broad minimum of low amplitude (<0.1 × 10−4) whereas in Er₂Co₁₇ as very sharp and large shrinkage (2.6 × 10−4). Thus, both the magnetoacoustics and magnetostriction are rather different in Tm₂Co₁₇ and Er₂Co₁₇. This supports different nature of the field-induced transitions in these compounds.